Longtail stingray Dasyatis longa, (Myliobatiformes: Dasyatidae) catches in the artisanal fisheries of Golfo Dulce, Costa Rica. - López-Garro, Andrés; Zanella, Ilena (Revista de Biología Tropical, 2015)
From May 2010 until May 2011, the longtail stingrays (Dasytis longa), caught by artisanal fishermen in Golfo Dulce, south Pacific of Costa Rica, were analyzed. We observed a total of 30 artisanal fishing operations in different areas of Golfo Dulce, with muddy bottoms and very shallow waters (less than 30m). The areas called “Los Bajos” and “Pique Fijo” represented the 26.7% and 23.3% of all the operations, respectively. Other important areas were “La Cienaga” (20.0%), “Lapa-Ríos” (6.7%) “Piedra del Sombrero” (6.7%) and “Pavones” (6.7%). “Matapalo”, “Corcovado” and “Punta Banco” were less used by fishermen (9.9% of trips). In the captures, 345 (39.6%) were sharks (Sphyrnidae Carcharhinidae, Heterodontidae, Ginglymostomatidae and Triakidae), 228 (26.1%) bait fish (Aridae), 112 (13.1%) rays (Dasyatidae, Myliobatidae, Rhinobatidae and Mobulidae) and 111 (12.7%) commercial fish (Lutjanidae, Serranidae, Sciaenidae). The most abundant ray was D. longa, with 75.7% of total rays caught, n=112), and more than 10% of total catch. The longtail stingrays male: female ratio was 1.33:1. Mean width disc length was 84.63±12.11cm. The highest Catch per unit effort, CPUE, was in January-February (0.006 stingrays per hook per hour). The lowest was in July and August (0.0004). Nearly all rays caught were released. We recommend regulations on the artisanal bottom line during from January to February in the areas of Los Bajos, Pique Fijo, and La Cienega.